Analysis of Mechanical Properties of CD 304 SS at High-Temperature Transient Conditions - Adi Prastyo; Fauzi Ibrahim; Mohammad Badaruddin (Jurnal POLIMESIN, 2022)
The mechanical properties of stainless steel at high temperatures are important parameters of the refractory design of stainless-steel structures. In this study, the mechanical properties of SS304 cold-drawn austenitic stainless grade at high temperature and room temperature were investigated experimentally. Thermal strain testing and total deformation of temperature transient conditions were carried out. The young modulus of maximum tensile is determined and the yield strength is determined using the 0.2% offset method. Temperature variables in this test are 25 °C, 100 °C, 200 °C, 300 °C, 400 °C, 500 °C, 600 °C, 700 °C, 800 °C, and 900 °C. In the thermal tensile test results, the specimen at 25 ° C has the highest ultimate voltage (σu), which is 698.33 MPa. Effect of temperature on the strength of SS304 stainless grade dramatically in the temperature range 700 °C. High temperatures reduce steel properties to a relatively greater degree, resulting in a decrease in the mechanical properties of stainless steel SS304 grade followed by relatively low steel ductility capabilities. SEM results explain that the formation of ε-martensite resulting from cold plastic deformation can lead to failure of the material at the total deformation of transient temperatures at low temperatures. The high chromium (Cr) content (~18%. wt) in grade CD 304 SS can be the main trigger for the formation of Cr-carbide precipitates formed in austenite grains or grain boundaries.